La paura (e non solo) di Montalbano. Su alcune locuzioni dialettali legate alla sfera sensoriale ed emotiva nei polizieschi di Andrea Camilleri (Carte Romanze, 2024)
In Andrea Camilleri’s detective novels, Sicilian dialect seems to perform the fundamental function of representing emotions and feelings, which are anything but fictitious: from fear and astonishment to despondency and shame, passing through boredom and torpor, Camilleri’s emotional lexicon seems to be diatopically marked. In order to offer a sample of this writing practice, in this contribution we will examine some strictly dialectal syntagmas expressing emotions, feelings or physical sensations, which can be found within the first four novels of the Montalbano series: La forma dell’acqua, Il cane di terracotta, Il ladro di merendine and La voce del violino.